Fabrication and evaporation time investigation of water treatment membranes using green solvents and recycled polyethylene terephthalate. Issue 35 (22nd July 2022) - Lu, David; Babaniamansour, Parto; Williams, Alex; Opfar, Kassandra; Nurick, Parker; Escobar, Isabel C.
Abstract: Many materials traditionally used for polymeric membrane fabrication incur significant environmental impacts and limit sustainability of the process; therefore, more eco‐friendly materials are needed in membrane fabrication. In this study, recycled polyethylene terephthalate (rPET) and a solvent blend of Rhodiasolv® PolarClean (PolarClean) and gamma‐valerolactone (GVL) were used as eco‐friendly materials to fabricate polysulfone (PSf) ultrafiltration membranes. The calculated Hansen solubility parameter affinity and relative energy difference values for PET and PolarClean‐GVL of 6.94 and 0.86, respectively, indicate favorable dissolution to create the preceding dope solution. At a baseline evaporation time of 30 s, the resulting rPET‐PSf/PolarClean‐GVL membranes outperformed the filtration capabilities of PSf/NMP membranes with 3.5% higher permeability (23.4 LMH/bar) and 53.2% greater rejection (84.9%) of bovine serum albumin (BSA). Increasing the evaporation time to 60 s resulted in a 32.4 LMH/bar decrease in permeability and 0.8% increase in BSA rejection, whereas decreasing the evaporation time to 0 s generally led to a 235.8 LMH/bar increase in permeability and 4% increase in BSA rejection. The findings indicate the potential for eco‐friendly materials to serve as alternatives for traditional materials in polymeric membranes. Abstract :